2019
DOI: 10.1002/ldr.3384
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of soil organic carbon in paddies during 13‐year conservation tillage

Abstract: Decreasing temporal variability of soil organic carbon (SOC) can avoid its temporary loss, which is positive to SOC accumulation and mitigation of climate change. Thus, this study was designed to analyze the temporal variability of SOC stock during 13‐year tillage practices and its driving factors in rice paddies of Southern China. Four tillage practices were studied: no‐till (zero‐tillage) with residues retained on the soil surface (NTS, conservation tillage), rotary tillage with incorporated residues (RTS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…The soil microbial CUE and MBC content with CT treatment were higher than that of RTO treatment. Similar results reported that rice yield and soil physicochemical properties of paddy field were increased through application of crop residue and tillage practice 3 , 4 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The soil microbial CUE and MBC content with CT treatment were higher than that of RTO treatment. Similar results reported that rice yield and soil physicochemical properties of paddy field were increased through application of crop residue and tillage practice 3 , 4 .…”
Section: Discussionsupporting
confidence: 82%
“…Soil organic carbon (SOC) content is affected by soil microorganism 2 . In the previous research, the results showed that SOC with no-tillage (NT) were lower than that of rotary and moldboard plow tillage with incorporated residue 3 , 4 . However, some studies showed that reduced tillage with rice residue retention increases the SOC content compared with conventional tillage (CT) and NT 5 .…”
Section: Introductionmentioning
confidence: 94%
“…After using different tillage methods for 11 years, in the 0–10 cm soil depth, the ZT had the highest SOC and N storage followed by PZT and then PT. Zero tillage can effectively increase SOC and N storage in surface soil (Qi et al, 2019; Xue et al, 2018). This improvement may be caused by the cover crop residue, which could have helped in storing supplemental soil C and N; however, it could be caused by the lower C and N emission in a zero‐tillage system compared with that in a ploughing‐tillage system (Han, Ning, Li, & Cao, 2014; Lu & Liao, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, large areas of soil have been degraded globally, with on- and off-site erosion ( Kara et al, 2016 ) followed by reductions in soil organic carbon (SOC) ( Gibbs & Salmon, 2015 ). Increasing the chelation or accumulation of SOC can effectively improve soil quality, reduce the risk of degradation ( Qi et al, 2019 ), and increase grain yields ( Uslu et al, 2020 ). The components of grain yields depend on and compensate for each other with changes in soil conditions ( Xu et al, 2019 ), and improper tillage measures can change soil conditions, making it vulnerable to severe degradation, resulting in lower yields, and further increasing the risk of food insecurity ( Doni et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%